Interfaith Marriage Phenomenon in Indonesia from the Perspective of Sadd al-Żarī'ah and Fatḥ al-Żarī'ah - Abdul Syatar; Muhammad Fazlurrahman Syarif; Harwis Alimuddin; Kurniati Kurniati; Rasna Rasna (IAIN Padangsidimpuan, 2023)
The subject of interfaith marriage in Indonesia, including its pros and cons, has been in the public purview recently. This research aims to answer public concerns, provide recommendations for strengthening regulations, and even prevent this type of marriage. A qualitative method alongside a sociological approach was applied, while data collection techniques included interviews and literature studies. It was concluded through sadd al-żarī'ah analysis, that interfaith marriage should be prohibited as it only leads to harm and difficulties in households and families. Furthermore, fatḥ al-żarī'ah analysis of the marriage of a Muslim man to an Ahlu al-Kitab woman is permitted by the majority of scholars. This is due to the possibility of benefits, namely the opportunity to guide the woman to embrace Islam. it is emphasized that this possibility is relative, as the Muslim man may change his faith. Therefore, this facility (al-żarī'ah) should not be opened (fatḥ al-żarī'ah). The implications of this study recommend sadd al-żarī'ah as material for consideration in strengthening the rules regarding interfaith marriages in the future. Moreover, the polemic of interfaith marriage should be resolved immediately by affirming and enforcing changes to the marriage law. Legal vacuums in the regulation of this matter should not be allowed or ignored due to the negative impact in terms of social and religious life.